1994
DOI: 10.1007/bf00193414
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigations on the human entorhinal area: left-right asymmetry and age-related changes

Abstract: Abstract.The total nerve cell numbers in the right and in the left human entorhinal areas have been calculated by volume estimations with the Cavalieri principle and by cell density determinations with the optical disector. Thick gallocyanin-stained serial frozen sections through the parahippocampal gyrus of 22 human subjects (10 female, 12 male) ranging from 18 to 86 years were analysed. The laminar composition of gallocyanin (Nissl)-stained sections could easily be compared with Braak's (1972Braak's ( , 1980… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 76 publications
2
44
1
Order By: Relevance
“…Section thickness cannot be directly read from the microtome. It must be optically determined in unstained as well as stained sections (for details see [58]). Due to staining, dehydration, and mounting procedures section thickness linearly decreases by about 20% to 480-540 !-lm.…”
Section: Methodsmentioning
confidence: 99%
“…Section thickness cannot be directly read from the microtome. It must be optically determined in unstained as well as stained sections (for details see [58]). Due to staining, dehydration, and mounting procedures section thickness linearly decreases by about 20% to 480-540 !-lm.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently it was generally believed that age-related impairments in cognitive performance are the result of age-related neuron loss, especially within the hippocampus and most neocortical areas. However, with the development of more accurate stereological techniques, it emerged that there is limited neuron loss within the hippocampal region (hilus and subiculum) and that there is no evidence of a more extensive neuronal loss than 10% during normal brain aging in other brain regions [20], including the MTL [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, such equipment is not readily available in most laboratories. This led investigators either to tailor their sampling design so that the section thickness need not be known (Cruz-Orive, 1987;Pakkenberg & Gundersen, 1989;Guntinas Lichius et al, 1993) or to develop alternative methods for measuring the vertical displacement of the microscope stage (Laroye & Taylor, 1992;Heinsen et al, 1994). One of these alternatives is to calibrate the scale of the fine focus knob with microscope cover glasses.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is that the vertical distance travelled by the microscope stage during focusing through a cover glass with a known thickness correlates linearly with the angular displacement of the fine focus knob. Such a calibration method has been described by Heinsen et al (1994). They found that one of the 200 gradation marks on the fine focus knob represented a stage movement of 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation